UCTEx Urdaneta Central Terminal Exchange enhancing urban mobility in Urdaneta City through a low-carbon intermodal transport hub - Fontanilla, Roemer Jan T.; Simoun T. Ong (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
This thesis addresses a problem existing in the country today- the lack of proper public transport provision, while also addressing associated challenges in the economy and the natural environment. Studies have found that long-term economic growth is influenced by the co-development of transportation infrastructure and several other sectors. Studies suggest that proper transport systems attract businesses and other investments responsible for urbanization and economic growth. However, separate studies have also reported varying levels of economic growth, which are inversely proportional to a locale's present level of development. Existing literature also indicates a link between inadequate public transport systems and environmental degradation. Sources state that the transportation sector is the second-highest contributor to carbon emissions - the main cause of global warming. Multiple studies have proposed a modal shift towards public and alternative forms of transportation as a direct response to decreasing global carbon emissions. This study addresses the issues in public transportation and the associated challenges regarding economic decline and environmental degradation in Urdaneta City. This study explored the use of low-carbon developments to provide further offset to carbon emissions and promote sustainable development in the area. This study utilized a combination of passive cooling techniques, sun-shading, energy harvesting technology, and green architecture to promote a conversion to new architectural design styles for public transport facilities. By dealing with the issues in public transportation in Urdaneta City, through the design of a low-carbon intermodal transport hub, the issues of economic decline and environmental degradation were also addressed.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Sustainable transportation -- Urdaneta City; Terminals (Transportation) -- Urdaneta City; Transportation -- Urdaneta City; Containerization -- Urdaneta City